DEVELOPMENT OF HEALTH PROMOTION PROGRAM BASED ON SOCIAL AND EMOTIONAL LEARNING CONCEPT FOR REDUCING RISKY SEXUAL BEHAVIORS IN UPPER SECONDARY SCHOOL STUDENTS - Sattayathewa, Pongnatee; Wattanaburanon, Aimutcha; Kay, Noy S. (Scholar: Human Sciences, 2018)
The purposes of this research were 1) to develop the health promotion program based on the social and emotional learning concept for reducing risky sexual behaviors in upper secondary school students in Thailand 2) to study the effects of the health promotion program based on the social and emotional learning concept on risky sexual behaviors in upper secondary school students in Thailand. The health promotion program was developed by using the social and emotional learning concepts. Then, the program was used for studying the effects on risky sexual behaviors in upper secondary school students in Thailand. With the purposive random sampling, a high school in Bangkok was selected and the sample (n = 60) was divided equally into two groups, the experimental group (n = 30) were assigned to participate under the health promotion program and the other students in control group (n = 30). The research findings were as follow; 1) a developed health promotion program based on the social and emotional learning concept for reducing risky sexual behaviors consisted of concept, 6 intervention activities and evaluation. 2) The effects of applying the health promotion program on risky sexual behaviors in experimental group were found lower than before at the .05 level of significance and found lower than students in control group at .05 the level of significance as well.